First record of late Carboniferous palynoassemblage from Ganmachidam Formation, Spiti Valley: Implications for age assessment and extent of Glossopterid elements in the Tethyan realm. Issue 6 (4th February 2022) - Gupta, Suyash; Saxena, Anju; Shabbar, Husain; Murthy, Srikanta; Singh, Kamal Jeet; Bali, Rameshwar
Abstract : The present work elucidates miofloral records from the Ganmachidam Formation (late Carboniferous–earliest Permian) of Spiti Valley, Tethyan Himalaya. The Ganmachidam Formation was hitherto considered as unfossiliferous, both for the faunal as well as floral records, and has been subjected to contentious age assessment. The present study has been carried out to find out the microfloral remains, assess the palynostratigraphic status, and the age of the Ganmachidam Formation. From the splintery shale sequence, a rich assemblage of palynomorphs has been recovered, having a dominance of monosaccate pollen grains, namely Parasaccites ( Cannanoropollis ), Crucisaccites, Divarisaccus, Densipollenites, Maculatasporites, followed by diverse bisaccate pollen grains, namely Scheuringipollenites, Crescentipollenites, Faunipollenites ( Protohaploxypinus ), Lunatisporites, Striatopodocarpites, Striatites, Rhizomaspora, Primuspollenites, and the spores Callumispora ( Punctatisporites ) and Calamospora in addition to woody fragments and fungal spores. Three palynoassemblages are identified. The recovered palynocomposition is corroborated with known records of palynomorphs from the Tethyan realm of India and from the late Carboniferous–Early Permian records of contemporaneous sequences across the globe. The composition of these palynoassemblages shows close correlation with the Crucisaccites monoletus Zone and Vittatina costabilis Interval Zone in the northeastern area of the Paraná Basin, Brazil, and lower Barakar palynozone ( Scheuringipollenites barakarensis Assemblage Zone) of Peninsular India which indicates the studied section of the Ganmachidam Formation is late Pennsylvanian to early Permian in age. Moreover, occurrences of palynomorphs from the Carboniferous sequences having a glossopterid affinity further strengthen the idea that glossopterids might have originated in Carboniferous time. Abstract : The present study shows the first record of palynomorphs from the unfossiliferous Ganmachidam Formation, Spiti valley, Tethyan realm. The recovered palynomorphs and their global correlation suggest that the age of the Ganmachidam Formation is late Pennsylvanian–Early Permian. The occurrence of the palynomorphs of Glossopteridales along with Coniferales and Cordaitales affinities suggests the existence of glossopterids during the Carboniferous times.